The Usefulness of Evaluating Performance of Activities in Daily Living in the Diagnosis of Mild Cognitive Disorders - Patricia De Vriendt (MDPI AG, 2021)
The Assessment of Activities of Daily Living (ADL) is paramount to ensure the accurate early diagnosis of neurocognitive disorders. Unfortunately, the most common ADL tools are limited in their use in a diagnostic process. Hence, we set out to validate a tool to evaluate basic (b-), instrumental (i-), and advanced (a-) ADL called the Brussels Integrated Activities of Daily Living Inventory (BIA). At the geriatric day hospital of the University Hospital Brussels (Belgium) older persons (65+) labelled as Cognitively Healthy Persons (CHP) (n = 47), having a Mild Cognitive Impairment (MCI) (n = 39), and having Alzheimer’s disease (AD) (n = 44) underwent a diagnostic procedure for neurocognitive disorders. Additionally, the BIA was carried out. An exploration using both (cumulative) logistic regressions and conditional inference trees aimed to select the most informative scales to discriminate between the HCP, persons with MCI and AD. The distinction between CHP and MCI and between MCI and AD was moderately successful with the i-ADLs, in addition to age. Therefore, it is advisable to conduct a multidomain assessment in which the i-ADL could serve as non-invasive and non-time-consuming screening, while the BIA might be useful for diagnostics and disease management.